2012
DOI: 10.1371/journal.pone.0033148
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lactoferrin Alleviates Age-Related Lacrimal Gland Dysfunction in Mice

Abstract: BackgroundDecrease in lacrimal gland secretory function is related to age-induced dry eye disease. Lactoferrin, the main glycoprotein component of tears, has multiple functions, including anti-inflammatory effects and the promotion of cell growth. We investigated how oral administration of lactoferrin affects age-related lacrimal dysfunction.Methods and FindingsTwelve-month-old male C57BL/6Cr Slc mice were randomly divided into a control fed group and an oral lactoferrin treatment group. Tear function was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 47 publications
4
40
0
Order By: Relevance
“…The prevalence of any corneal disease by age was low in early and later life stages. Of the corneal disease patients, fewer than 8% were aged 20 or younger (5.85% for those aged 0-9 and 7.04% for those aged [10][11][12][13][14][15][16][17][18][19], only 4.53% were aged 70 to 79 years, and only 1% were 80 and older. Most of the patients with corneal disease were aged between 30 and 59 years, with 16.29% at 30 to 39 years, peaking at 22.04% for ages 40 to 49, and remained high at ages 50 to 59 (21.05%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of any corneal disease by age was low in early and later life stages. Of the corneal disease patients, fewer than 8% were aged 20 or younger (5.85% for those aged 0-9 and 7.04% for those aged [10][11][12][13][14][15][16][17][18][19], only 4.53% were aged 70 to 79 years, and only 1% were 80 and older. Most of the patients with corneal disease were aged between 30 and 59 years, with 16.29% at 30 to 39 years, peaking at 22.04% for ages 40 to 49, and remained high at ages 50 to 59 (21.05%).…”
Section: Resultsmentioning
confidence: 99%
“…Corneal degeneration (3.90%), chemical burn (3.55%), and corneal dystrophy (3.19%) all occurred among those aged 20 to 29 years (Table 6; P < 0.01). Other common noninfectious corneal diseases, such as staphyloma (1.83%), keratoconus (21.29%), and corneal leucoma (10.96%) occurred in younger age groups (ages [10][11][12][13][14][15][16][17][18][19]. The highest incidence of perforating injury (1.65%) was observed among those aged 0 to 9 years.…”
Section: Resultsmentioning
confidence: 99%
“…7). 53,54 Oxidative stress of the ocular surface may be controlled by other key molecules found in tear fluid such as prealbumin, selenoprotein, and other proteins. [55][56][57][58] …”
Section: Oxidative Stress and Dry Eyementioning
confidence: 99%
“…Several studies have already reported the beneficial effects of bLF on lipid metabolism in animals. Kawashima et al reported that 2 LF dietary supplementation significantly reduced serum non-esterified FA NEFA levels in 10-month-old C57BL/6Cr mice 7 while Takeuchi et al showed that bLF improved many lipid metabolism-related parameters 8 .…”
Section: Introductionmentioning
confidence: 99%